2015
DOI: 10.1016/j.molonc.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin specific protease 4 positively regulates the WNT/β‐catenin signaling in colorectal cancer

Abstract: β-catenin is a key signal transducer in the canonical WNT pathway and is negatively regulated by ubiquitin-dependent proteolysis. Through screening of various deubiquitinating enzymes (DUBs), we identified ubiquitin specific protease 4 (USP4) as a candidate for β-catenin-specific DUB. The effects of USP4 overexpression or knockdown suggested that USP4 positively controls the stability of β-catenin and enhances β-catenin-regulated transcription. Domain mapping results revealed that the C-terminal catalytic doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 44 publications
(49 reference statements)
2
88
0
Order By: Relevance
“…TRABID also positively regulates Wnt signaling by deubiquitylating adenomatous polyposis coli (APC) and regulating the stability of the β-catenin/ TCF transcription complex (18). USP47 and USP4 can directly regulate β-catenin deubiquitylation (19,20). USP8 deubiquitylates endosome-tethered Fzd, resulting in the recycling of Fzd to the plasma membrane (21).…”
mentioning
confidence: 99%
“…TRABID also positively regulates Wnt signaling by deubiquitylating adenomatous polyposis coli (APC) and regulating the stability of the β-catenin/ TCF transcription complex (18). USP47 and USP4 can directly regulate β-catenin deubiquitylation (19,20). USP8 deubiquitylates endosome-tethered Fzd, resulting in the recycling of Fzd to the plasma membrane (21).…”
mentioning
confidence: 99%
“…Ubiquitin specific peptidase 4 function is important during tumorigenesis because this deubiquitinating enzyme has a key role in the regulation of TP53 and TGFβ signaling and is also a positive regulator of the WNT/β-catenin signaling [18][19][20]. Deubiquitinating enzyme UPS10 suppresses the proliferation and growth of cancer cells through stabilization of p53 protein [21].…”
mentioning
confidence: 99%
“…USP4 overexpression is correlated with numerous types of cancer because it deubiquitinates ubiquitin-conjugated proteins. Wnt/b-catenin signalling is a significant pathway in osteoblast differentiation and is also modulated by USP4 [62,63]. USP4 affects neuronal apoptosis in the intracerebral hemorrhage pathway [53], which could be correlated with human breast cancer migration and invasion by promoting relaxin/transforming growth factor-b1/ Smad2/matrix metallopeptidase 9 signalling [54], and also modulates the activation of transforming growth factor b-activated kinase 1-(JNK1/2)/p38 signalling in cardiac hypertrophy [55].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, USP4 has important roles in DNA-end resection and DNA repair [4], p53 and NF-jB signalling [59], homologous recombination [60] and DNA double-strand breaks [61]. Wnt/b-catenin signalling is a significant pathway in osteoblast differentiation and is also modulated by USP4 [62,63]. Recently, it was found that USP4 interacts with programmed cell death 4, thereby repressing cell proliferation in breast cancer cells [64].…”
Section: Discussionmentioning
confidence: 99%